(untitled) (Research, Society and Development, 2021)
Due to the effectiveness in disease prevention and health promotion, the consumption of functional and nutraceutical foods has increased more and more. In this sense, the egg is included in this class of foods, as it is one of the most economical sources of protein for the human diet, it has in its composition lipids, vitamins and high quality minerals. Eggs have a high potential for enrichment with polyunsaturated fatty acids (PUFAs) by supplementing the diet of laying hens with ingredients that contain this type of fatty acid, resulting in increased deposition of omega-3 in the egg yolk. Fishmeal is an example of an ingredient that can be included in poultry diets, as it has a considerable amount of amino acids, vitamins and PUFAs. The inclusion of fishmeal in laying diets can improve the immune response of birds and humans, PUFAs help in the prevention and treatment of various diseases, decrease levels of circulating triglycerides and participate in the structure and function of the brain. In addition to easy inclusion in laying diets, fishmeal promotes rapid modification in the lipid composition of egg yolk and helps in the disposal of waste from agroindustry. A literature search was carried out on the internet of articles included in the inclusion of fishmeal in the diet of laying hens from 2005 to 2020. The objective of this study was to find positive points that leverage the use of this by-product in poultry diets.